Monster Vision - Leroe, Ellen, 1949. (New York : Hyperion Books for Children, 1996)
When a mixed-up mail delivery causes twelve-year-old Jamie to put in contact lenses belonging to a dead magician, his eyeless ghost appears to demand them back.
All age.
Keywords: Ghosts -- Fiction; Horror stories